Grid Connected Multilevel Inverters For PV Application - Suziana, Ahmad; Siti Halma, Johari; Mohd Firdaus, Mohd Ab Halim; Arfah, Ahmad (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
Due to the high electricity demand and the decreasing of fossil fuel sources, most of the countries around the world goes to renewable energy such as wind, tidal and photovoltaic (PV) for electricity generation. Among these, the study of PV as an alternative source for electricity generation has gain wide attention. One of the important aspects that should be considered in PV application is the use of grid connected multilevel inverter. This work focuses on three phase diode clamped multilevel inverter, capacitor clamped multilevel inverter and H-cascaded bridge multilevel inverter for connecting grid and PV application. These three types of multilevel inverters were simulated in Matlab-Simulink environment and a multicarrier pulse width modulation (PWM) was used for the control methods. The output waveforms of multilevel inverters are presented and comparison between these are given. The best topology for a grid connected multilevel inverter for PV application is recommended.